2020
DOI: 10.1155/2020/7421769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corn Stalk Fly Ash (CSFA) on the Mechanical and Deformation Properties of Cemented Coal Gangue Backfill

Abstract: To reduce the amount of cement used in cemented coal gangue backfill (CCGB, a mixture of coal gangue, cement, fly ash, and water), mechanical and deformation properties of CCGB in which CSFA partially replaces the cement (0, 10, 20, 30, and 40 wt%) were studied. Compressive strength, acoustic emission during uniaxial loading, shear strength, and drying shrinkage were analysed. The compressive strength, shear strength, and drying shrinkage tests were performed at different curing times. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The materials used in the test include coal gangue, fly ash, corn straw fly ash, cement and water, and their physical and chemical properties can be referred to [17,18,34]. According to the previous research results and other researchers' work, coal gangue is mainly composed of silicon dioxide (SiO2) and aluminum oxide (Al2O3) [35][36][37].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The materials used in the test include coal gangue, fly ash, corn straw fly ash, cement and water, and their physical and chemical properties can be referred to [17,18,34]. According to the previous research results and other researchers' work, coal gangue is mainly composed of silicon dioxide (SiO2) and aluminum oxide (Al2O3) [35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al, [17] showed that replacing the same amount of fly ash with the same amount of corn straw fly ash can effectively improve the compressive strength of backfill. Qi et al, [18] investigated the substitution of corn straw fly ash for part of cement in the slurry and concluded that the compressive strength and drying shrinkage ratio of the filling body were the best when the replacement rate was 20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because incineration ash usually exhibits pozzolanic activity, other types of incineration ash have also been applied as SCMs for CLSM production. These include incineration sludge ash, such as waste paper sludge ash (WPSA) [16], incineration sludge ash [17], and mixed incineration sludge ash [18]; garbage incineration ash, such as domestic waste incinerator bottom ash [19] and industrial waste incineration bottom ash [20]; and biomass incineration ash, such as wood ash [21], corn straw ash [22,23], rice straw ash [24] and bagasse ash [25]. Among the metallurgical industrial by-products, blast-furnace slag is often used as an SCM for CLSM production, due to its high hydration activity.…”
Section: Clsm Strengthmentioning
confidence: 99%
“…Maize straw ash is the burnt residue of the leaves, stalks, and cobs of maize plants left on the field after harvest [14]. MSA possesses substantial pozzolanic properties and a large amount of silica [15]. However, only a few studies have been conducted on its use in concrete.…”
Section: Introductionmentioning
confidence: 99%